Optimization of Asynchronous Electric Generator Parameters in System Wind Power Installations - Yu. V. Makosko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a wind power installation with asynchronous electric generator which is integrated in large power system. Mathematical model describing a wind motor, an asynchronous generator, step-up transformers, cable and open-air electric power lines has been used to obtain linear polynomials. These polynomials make it possible to investigate the influence of asynchronous generator parameters and average wind velocity on quasi-stationary operational conditions of a system wind power installation. Methodology on selection of optimum active resistance quantity for a short-circuited winding of an asynchronous generator rotor in a system wind power installation has been elaborated